1992
DOI: 10.1038/359412a0
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for extensive paternal mitochondrial DNA inheritance in the marine mussel Mytilus

Abstract: Inheritance of mitochondrial DNA in animals was thought to be strictly maternal. Recently, evidence for incidental paternal mtDNA leakage was obtained in hybrid crosses of Drosophila and mice. In mice, the frequency of paternal mtDNA contributions was estimated at 10(-4), compared with maternal contributions. The common occurrence in the marine mussel Mytilus of heteroplasmic individuals with two or more types of highly diverged mtDNA molecules was interpreted as strong evidence for biparental mtDNA inheritanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
113
2
11

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(129 citation statements)
references
References 19 publications
3
113
2
11
Order By: Relevance
“…At present, the occurrence of paternal leakage remains heteroplasmic, containing different mitochondrial allelic types. During past years, many studies have shown controversial, except for some peculiar inheritance systems as in mussels, where paternal transmission has that heteroplasmy may be more common than previously thought, due to the constant input of new mutabeen clearly demonstrated (Zouros et al 1992;Skibinski et al 1994). In Drosophila, paternal transmission tions (Corral-Debrinski et al 1992;Cortopassi et al 1992;Jazin et al 1996;Lightowlers et al 1997;Michi-has been detected in both interspecific and intraspecific crosses (Kondo et al 1990(Kondo et al , 1992.…”
mentioning
confidence: 99%
“…At present, the occurrence of paternal leakage remains heteroplasmic, containing different mitochondrial allelic types. During past years, many studies have shown controversial, except for some peculiar inheritance systems as in mussels, where paternal transmission has that heteroplasmy may be more common than previously thought, due to the constant input of new mutabeen clearly demonstrated (Zouros et al 1992;Skibinski et al 1994). In Drosophila, paternal transmission tions (Corral-Debrinski et al 1992;Cortopassi et al 1992;Jazin et al 1996;Lightowlers et al 1997;Michi-has been detected in both interspecific and intraspecific crosses (Kondo et al 1990(Kondo et al , 1992.…”
mentioning
confidence: 99%
“…Crosses between Mytilus edulis with rather divergent mtDNA showed total exclusion of paternal mtDNA within oocytes, whereas incomplete exclusion of maternal mtDNA took place within sperm (Zouros et at., 1992;Skibinski et a!., 1994). Following a paternal contribution, a given individual has heteroplasmic somatic cells whenever its parents did not carry the same mtDNA type and the nature of its progeny (homoplasmic or heteroplasmic) will mostly depend on the type of mtDNA of its mate.…”
mentioning
confidence: 99%
“…The Unionidae and two other bivalve families (Mytilidae and Veneridae) possess two different mitochondrial genomes (mitotypes) that are associated with gender (F for female and M for male) (Zouros et al, 1992(Zouros et al, , 1994Hoeh et al, 1996Hoeh et al, , 1997Liu et al, 1996;Passamonti & Scali, 2001). These sexual mitotype lineages remain separate via doubly uniparental inheritance (DUI) (Skibinski et al, 1994;Zouros et al, 1994), where the maternal mitochondrial genome (F-mitotype) is inherited by both male and female progeny from the mother, while the paternal mitochondrial genome (M-mitotype) is only transmitted from father to male offspring and housed in the male gonads.…”
mentioning
confidence: 99%